Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s10384-013-0244-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of human T lymphotropic virus type 1-associated uveitis in Hokkaido, Japan

Abstract: A number of clinical features were unique to Hokkaido, namely, predominant unilateral involvement, as well as two HAU patients with ATLL. The phylogenetic difference of HTLV-1 and HLA typing may correlate with different clinical manifestations in HAU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The most frequently reported HTLV-1associated ocular disease is HU (Kamoi and Mochizuki, 2012b). Ophthalmologists have reported on HU from Hokkaido to Kyushu, with cases described from all over Japan (Mochizuki et al, 1992b;Goto et al, 1994;Kawamoto and Hayasaka, 1994;Ohba et al, 1994a,b;Ishioka et al, 1995;Takahashi et al, 2000;Miyanaga et al, 2009;Kase et al, 2013;Terada et al, 2017a). As for other areas of the world, clinical research into HU has been reported from the United States (Beilke, 1995), Martinique (Merle et al, 1996), Britain (Sandy et al, 1996), and Brazil (Yamamoto et al, 1999).…”
Section: Htlv-1 Carriers and Ocular Diseasementioning
confidence: 99%
“…The most frequently reported HTLV-1associated ocular disease is HU (Kamoi and Mochizuki, 2012b). Ophthalmologists have reported on HU from Hokkaido to Kyushu, with cases described from all over Japan (Mochizuki et al, 1992b;Goto et al, 1994;Kawamoto and Hayasaka, 1994;Ohba et al, 1994a,b;Ishioka et al, 1995;Takahashi et al, 2000;Miyanaga et al, 2009;Kase et al, 2013;Terada et al, 2017a). As for other areas of the world, clinical research into HU has been reported from the United States (Beilke, 1995), Martinique (Merle et al, 1996), Britain (Sandy et al, 1996), and Brazil (Yamamoto et al, 1999).…”
Section: Htlv-1 Carriers and Ocular Diseasementioning
confidence: 99%
“…Human T lymphocyte virus type 1 (HLTV-1) is human retrovirus that targets CD4 lymphocytes of the adaptive immune system 15,16 . Transmission occurs via sexual contact, blood transfusion, and through breast milk 17 .…”
Section: Htlv-1 Associated Uveitismentioning
confidence: 99%
“…HTLV-1 is highly endemic in certain areas of the world including Southern Japan, the Caribbean, and central Africa. 15,18 . Inflammation is caused by intraocular infiltration of HTLV-1 infected T cells, viral gene expression, and release of cytokines including IL-6 15,19 .…”
Section: Htlv-1 Associated Uveitismentioning
confidence: 99%
See 2 more Smart Citations